A aplicação do principio da proporcionalidade às questões existenciais - Nakamura, Mario Massao (2014)
The doctrine has shown that the difference between rules and principles is characterized by a structural and content difference where rules are more specific and determined, and principles belong to an open set with a high degree of generality. The constitutionalization of civil law implied the verticalization of these principles throughout all the law system. This has led to rising conflicts between constitutionally protected individual rights mainly due to the horizontal efficacy verified in private relationships. As a means of conflict resolution, in case of conflicts involving constitutionally protected rights of the same hierarchy, we propose the application of proportionality rules. This is a well known tool in the constitutional area, but still of little use in private law practice